2006
DOI: 10.1016/j.jcrs.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patients with good uncorrected distance and near vision after monofocal intraocular lens implantation

Abstract: The study suggests a significant role of ATR corneal astigmatism in good uncorrected distance and near vision after monofocal IOL implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 34 publications
7
42
4
Order By: Relevance
“…13 The correlation between the axis of astigmatism and age is significant because residual postsurgical WTR astigmatism has been shown to result in better distance Snellen visual acuity than OB astigmatism, 4 whereas residual ATR results in better unaided distance and near vision in some pseudophakics. 21 This therefore poses the question as to whether corneal stigmatism should be treated more aggressively in younger patients where WTR astigmatism is most prevalent. However, with the increasing popularity of toric presbyopic (multifocal and depth-of-focus) IOLs this becomes less significant for patients who can afford to pay for premium IOLs with guaranteed multifocality and depth of focus.…”
Section: Discussionmentioning
confidence: 99%
“…13 The correlation between the axis of astigmatism and age is significant because residual postsurgical WTR astigmatism has been shown to result in better distance Snellen visual acuity than OB astigmatism, 4 whereas residual ATR results in better unaided distance and near vision in some pseudophakics. 21 This therefore poses the question as to whether corneal stigmatism should be treated more aggressively in younger patients where WTR astigmatism is most prevalent. However, with the increasing popularity of toric presbyopic (multifocal and depth-of-focus) IOLs this becomes less significant for patients who can afford to pay for premium IOLs with guaranteed multifocality and depth of focus.…”
Section: Discussionmentioning
confidence: 99%
“…OS has been observed following in-the-bag IOL implantation with different IOL types and designs with varying results. 3,5,7,8,11,12,23,24 OS using pharmacological technique has been demonstrated to be 0.0870.26 mm for polymethyl methacryclate (PMMA), 5 0.4270.46 mm for hydrogel IOL, 5 and 0.2870.38 mm for foldable silicone IOL. 25 Moreover, Fukasaku and Marron ('Accommodation' video presented at the XVIth Congress of the European Society of Cataract & Refractive Surgeons, Nice, France, September 1998), using ultrasound biomicroscopy, showed that the IOL moves anteriorly by a mean of 0.32 mm during near vision; whereas Lesiewska-Junk H and Kahuzny J showed a mean shift of 0.42 mm without any medication.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 We measured the OS by applying the pharmacological method in which we calculated the difference in the ACD. 3,10,11,24,[30][31][32][33][34][35] Although this is an indirect method, it is well-accepted as it does not rely on patient compliance during the measurement procedure. 3 Even though these pharmacological stimuli are nonphysiological, they are reported to be useful to find out the maximum potential of the optic shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 To further assess the outcomes of extreme myopia with cataract patients, a prospective randomized controlled study was investigated on eyes with a refraction ≥-10D and AL ≥ 27.0 mm that had phacoemulsification and implanted with monofocal IOL. Particular attention was directed toward the difference between the "actual" and "predicted" postoperative spherical refractive power with its influence factors, and the accommodation amplitude in comparison with non-myopic eyes.…”
Section: Introductionmentioning
confidence: 99%